Design of Web-Based Hajj Manasik Supervision Certification Information System - Agus Pamuji; Muzaki Muzaki; Heri Satria Setiawan (Indonesian Scientific Journal, 2022)
In the discussion of this research, the motivation to design a certification information system at the Regional Office (Kanwil) of the West Java Ministry of Religion seeks to resolve, and reduce the problem of the certification system which is not yet effective and far from efficient. The activities of implementing certification for offline (face-to-face) Hajj ritual supervisors, and processing certification data traditionally affect the results of recording certification and implementing the assessment process. Thus, the proposed system is generated through a website-based platform and is run online. The research method uses the System Development Life Cycle (SDLC) with the Waterfall model approach which consists of 5 stages, namely, a) Analysis b) Design c) Implementation d) Maintenance e) Planning. The programming language used is (PHP), and the database application uses a data processor (Mysql) as the database (RDBMS). In addition, to support this system design tool, it uses the UML (Unifed Modeling Language) method by using two diagrams according to design needs, namely Use Case Diagrams and Activity Diagrams. This research produces a Web-Based Certification Information System design that can simplify the certification implementation process, as well as simplify the presentation of certification data and its processing. The system of certification of Manasik Hajj supervisor have been test with a method. Black box testing is the most method to ensure the application is suitable scenario test. This Web-Based Hajj Manasik Supervisor Certification Information System at the West Java Ministry of Religion Regional Office makes it easier to improve the implementation of certification. The design of this system can reduce in addition to overcoming the obstacles of implementing certification to be more accurate.